1998
DOI: 10.1063/1.368874
|View full text |Cite
|
Sign up to set email alerts
|

Modified compensation model of CdTe

Abstract: The traditional compensation model to explain the high resistivity properties of CdTe is based on the presence of a deep acceptor level of the cadmium vacancy in the middle of the band gap. A new compensation model based on a deep intrinsic donor level is presented. The compensation model is used together with an appropriate segregation model to calculate axial distributions of resistivity which are compared with spatially resolved resistivity measurements. The Te-antisite defect is discussed as a possible ori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
99
0
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 199 publications
(103 citation statements)
references
References 24 publications
3
99
0
1
Order By: Relevance
“…The compensation between the deep-level Te antisites, the Cd interstitials, and the Cd vacancies is considered responsible for the high resistivity of CZT. 6,7 This compensation could be lost due to extra Cd interstitials introduced during annealing in Cd vapor, thereby shifting the Fermi level toward the bottom of the conduction band or the top of the valence band. Furthermore, we measured the lowtemperature PL spectrum of as-grown and annealed CZT (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The compensation between the deep-level Te antisites, the Cd interstitials, and the Cd vacancies is considered responsible for the high resistivity of CZT. 6,7 This compensation could be lost due to extra Cd interstitials introduced during annealing in Cd vapor, thereby shifting the Fermi level toward the bottom of the conduction band or the top of the valence band. Furthermore, we measured the lowtemperature PL spectrum of as-grown and annealed CZT (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…CdTe:Bi doped crystals were grown by the vertical Bridgman method using different dopant concentrations from 10 17 -10 19 at./ cm 3 . Samples of 10ϫ 10ϫ 1.5 mm 3 were cut, and then mechanically and chemically polished as was previously reported.…”
Section: Methodsmentioning
confidence: 99%
“…1,2 Deep levels play a key role on the electrical and transport charge properties of CdTe, determining the final detector's performance. [3][4][5][6] For example, has been demonstrated that the presence of these recombination deep centers is the mainly reason of the polarization effect of detectors, leading to the collapse of their internal electric field. The mechanism has been interpreted by the accumulation of charges in these recombination centers.…”
Section: Introductionmentioning
confidence: 99%
“…Undoped GaTe is p-type with low resistivity ͑20 ⍀ ·cm͒ and low mobility ͑15 cm 2 / V·s͒. 2 To meet radiation detector application requirements ͑resistivityϾ 1 ϫ 10 9 ⍀ · cm, mobilityϳ 1 ϫ 10 3 cm 2 / V·s͒, the material should possess deep levels near the middle of the band gap, 13 and dopants have to be introduced into the material to compensate the native shallow acceptors. The type and intensity of both intrinsic and extrinsic defects have influence on the fundamental properties of GaTe; it is important to study defect levels between the valence and the conduction bands of GaTe crystals.…”
Section: Introductionmentioning
confidence: 99%